2016
DOI: 10.1038/ncomms10746
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light-chain phosphatase regulates basal actomyosin oscillations during morphogenesis

Abstract: Contractile actomyosin networks generate forces that drive tissue morphogenesis. Actomyosin contractility is controlled primarily by reversible phosphorylation of the myosin-II regulatory light chain through the action of myosin kinases and phosphatases. While the role of myosin light-chain kinase in regulating contractility during morphogenesis has been largely characterized, there is surprisingly little information on myosin light-chain phosphatase (MLCP) function in this context. Here, we use live imaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…This transmitted force can either persist as tension in the epithelium, or it can resolve with the displacement of cell junctions and actomyosin toward the center of the contraction. Actomyosin pulses also often correspond with an accumulation and dissipation of F-actin (Blanchard et al, 2010; He et al, 2010; Mason et al, 2013; Rauzi et al, 2010; Valencia-Expósito et al, 2016). In some biological contexts, repetitive actomyosin pulses exhibit bona fide oscillatory behavior that can be identified as a dominant frequency using Fourier analysis (Gorfinkiel, 2016; Koride et al, 2014; Sokolow et al, 2012; Solon et al, 2009).…”
Section: The Pulsatile Behavior Of Nonmuslce Myosin 2 and Filamentousmentioning
confidence: 99%
See 1 more Smart Citation
“…This transmitted force can either persist as tension in the epithelium, or it can resolve with the displacement of cell junctions and actomyosin toward the center of the contraction. Actomyosin pulses also often correspond with an accumulation and dissipation of F-actin (Blanchard et al, 2010; He et al, 2010; Mason et al, 2013; Rauzi et al, 2010; Valencia-Expósito et al, 2016). In some biological contexts, repetitive actomyosin pulses exhibit bona fide oscillatory behavior that can be identified as a dominant frequency using Fourier analysis (Gorfinkiel, 2016; Koride et al, 2014; Sokolow et al, 2012; Solon et al, 2009).…”
Section: The Pulsatile Behavior Of Nonmuslce Myosin 2 and Filamentousmentioning
confidence: 99%
“…In developmental contexts, actomyosin pulsing was first reported in the C. elegans zygote, where pulsing is involved in establishing anterior-posterior polarity preceding the first cell division (Munro et al, 2004). Pulsing was later observed in the Drosophila embryo in several contexts: in apical constriction of epithelial cells of the ventral furrow (Martin et al, 2009), salivary gland (Booth et al, 2014), and renal tubules (Saxena et al, 2014); in constrictions of the amnioserosa cells during dorsal closure (Blanchard et al, 2010; David et al, 2010; Solon et al, 2009); during extension of the germband (Fernandez-Gonzalez and Zallen, 2011; Rauzi et al, 2010; Sawyer et al, 2011); and in the follicular epithelium surrounding and shaping the developing oocyte (He et al, 2010; Valencia-Expósito et al, 2016). They appear to shrink pre-existing cell contacts (Rauzi et al, 2010), and drive elongation of junctions, leading to tissue extension (Collinet et al, 2015; Yu and Fernandez-Gonzalez, 2016).…”
Section: The Pulsatile Behavior Of Nonmuslce Myosin 2 and Filamentousmentioning
confidence: 99%
“…In addition, we found that mutant cells displayed a more stochastic behavior than controls (Fig.S3C and Fig.S4C). Finally, we challenged our previous model and tested if reduced F-actin levels could lead to shorten and more stochastic oscillations, as well as reduced myosin levels 16 . We found this was the case (Fig.S3F-H), proving the robustness of the model.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the role of integrins on the organization of actomyosin fibers on the basal side of FCs remains controversial. The actomyosin fibers present on the basal side of FCs undergo oscillating contractions 13, 16 . Furthermore, these contractions and their coupling to the ECM are required for the cell shape changes underlying egg elongation 12, 13, 17, 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was demonstrated that a ROCK and myosin (light chain) phosphatase oscillator acts as a source for Drosophila ovarian epithelium oscillatory behavior of myosin [36]. A clear coupling of actin and myosin oscillations were also shown in [37]. The interaction of myosin with an atypical cortical actin pool was recently demonstrated to be relevant for myosin and/or membrane oscillations [38]: here, myosin contractility was found to be relevant for the erythrocyte 2D spectrin-F-actin network in membrane associated myosin foci.…”
Section: Introductionmentioning
confidence: 98%